Upaya Pencegahan Stunting Melalui Kegiatan Pemanfaatan Potensi Lokal Bersama Kader Kesehatan Di Kelurahan Guwosari - Jana, Padrul; Fitriani, Rosmauli Jerimia; Saptatiningsih, Rosalia Indriyati (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2024)
Alleviating stunting cases is still the main agenda that must be resolved immediately. Children with good nutrition and optimal growth and development will impact Indonesia's superior human resources. However, in some places, public knowledge about stunting and child nutrition still needs to be improved. This fact has encouraged the service team to carry out activities to mitigate stunting cases by utilizing potential sources of nutritious food in the environment. The method used is through three stages. The stages are counseling and assistance related to stunting, training on MP-ASI processing by utilizing local food potential, and assistance with nutritional consultations and child growth and development. The results achieved after this activity were increased public knowledge and understanding regarding stunting and prevention by providing nutritious food to children. Apart from that, people can also take advantage of highly nutritious food sources around the house at low prices and abundant availability. Based on the results of focus group discussions involving various parties, they received a very good response from the community, health cadres, sub-districts, and health officers from the sub-district.